2005
DOI: 10.1111/j.1600-0463.2005.apm_204.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and clinical significance of increased intraepithelial lymphocytes (IELs) in small bowel mucosa

Abstract: Intestinal intraepithelial lymphocytes (IELs) belong to a unique T-cell population interspersed between epithelial cells of both the small and large intestine. It is becoming increasingly recognised that an increased number of IELs with a normal villous architecture is within the wide spectrum of histological abnormalities observed in coeliac disease. An increased number of IELs is the earliest pathological change following gluten challenge and a high IEL count may be the only sign of gluten sensitivity. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 77 publications
4
54
1
1
Order By: Relevance
“…Large numbers of villous IELs was described during an episode of active Crohn's enteritis (29). However, Wright et al (30) found a similar IEL density in the duodenum of Crohn's disease patients with normal radiographic and endoscopic findings in agreement with our results.…”
Section: Discussionsupporting
confidence: 82%
“…Large numbers of villous IELs was described during an episode of active Crohn's enteritis (29). However, Wright et al (30) found a similar IEL density in the duodenum of Crohn's disease patients with normal radiographic and endoscopic findings in agreement with our results.…”
Section: Discussionsupporting
confidence: 82%
“…Helicobacter pylori infection has no major influence on the intraepithelial lymphocyte counts in children with recurrent abdominal pain or children with coeliac disease. [6][7][8][9] Increased IELs are also present in~70% of patients with noncoeliac enteropathy. 10 Furthermore, mild intraepithelial lymphocytosis has also been described in healthy individuals with varying prevalence in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-epithelial lymphocyte populations are known to increase in patients with various intestinal disorders [22] but the model we have used denudes the intestinal epithelium which would also preclude intra-epithelial lymphocytes from the CD4/IL-36-R population we have measured. Our results, therefore, most likely indicate that CD4+ lymphocytes maintain IL-36R expression as they enter peripheral tissue from the blood.…”
Section: Discussionmentioning
confidence: 99%